High Dk piggyback contact lens system for contact lens-intolerant keratoconus patients - Tomris Sengor (Dove Medical Press, 2011)
Tomris Sengor, Sevda Aydin Kurna, Suat Aki, Yelda ÖzkurtFatih Sultan Mehmet Training and Research Hospital, Istanbul, TurkeyBackground: The aim of the study was to examine the clinical success of high Dk (oxygen permeability) piggyback contact lens (PBCL) systems for the correction of contact lens intolerant keratoconus patients.Methods: Sixteen patients (29 eyes) who were not able to wear gas-permeable rigid lenses were included in this study. Hyper Dk silicone hydrogel (oxygen transmissibility or Dk/t = 150 units) and fluorosilicone methacrylate copolymer (Dk/t = 100 units) lenses were chosen as the PBCL systems. The clinical examinations included visual acuity and corneal observation by biomicroscopy, keratometer reading, and fluorescein staining before and after fitting the PBCL system.Results: Indications for using PBCL system were: lens stabilization and comfort, improving comfort, and adding protection to the cone. Visual acuities increased significantly in all of the patients compared with spectacles (P = 0). Improvement in visual acuity compared with rigid lenses alone was recorded in 89.7% of eyes and no alteration of the visual acuity was observed in 10.3% of the eyes. Wearing time of PBCL systems for most of the patients was limited time (mean 6 months, range 3–12 months); thereafter they tolerated rigid lenses alone except for 2 patients.Conclusion: The PBCL system is a safe and effective method to provide centering and corneal protection against mechanical trauma by the rigid lenses for keratoconus patients and may increase contact lens tolerance.Keywords: piggyback contact lens, keratoconus, irregular astigmatism